Pain and Interoceptive Awareness Outcomes of Chronic Pain Patients With Spinal Cord Stimulation. Issue 8 (15th November 2020) - Park, Yunseo Linda; Hunter, Jared; Sheldon, Breanna L.; Sabourin, Shelby; DiMarzio, Marisa; Khazen, Olga; Pilitsis, Julie G.
Abstract: Objectives: Meditation has been shown to improve outcomes for chronic pain by increasing patients' awareness of their own bodies. Some patients have an innate ability to leverage their mind–body connection, and this interoceptive awareness may aid them in garnering pain relief. We explored whether spinal cord stimulation (SCS) patients with greater innate awareness had better outcomes. Materials and Methods: We contacted 30 thoracic SCS patients with baseline and postoperative pain, psychological, and disability outcomes to complete the Multidimensional Assessment of Interoceptive Awareness (MAIA) survey. MAIA distinguishes between beneficial and maladaptive aspects of the perception of body sensations via six positive subscales (noticing, attention regulation, emotional awareness, self‐regulation, body listening, and trusting) and two negative subscales (not distracting, not worrying). MAIA subscales and positive/negative groups were correlated with percentage change in Numerical Rating Scale (NRS), Oswestry Disability Index (ODI), Beck's Depression Inventory (BDI), Pain Catastrophizing Scale (PCS), and McGill Pain Questionnaire (MPQ). Results: Patients included 14 males/16 females with a mean age of 58. At a mean follow‐up of 14.13 months (range 6–26), NRS, ODI, BDI, PCS, and MPQ showed improvements. Positive traits correlated with improvements in pain (MAIA‐self regulation with NRS‐worst [ p  = 0.018], NRS‐least [ p  = 0.042], NRS‐average [ p  = 0.006], NRS‐current [ p  = 0.001]; MAIA‐body listening with MPQ‐total [ p  = 0.016] and MPQ‐sensory [ p  = 0.026]). Improvement in PCS‐total was associated with higher scores in noticing ( p  = 0.002), attention regulation ( p  = 0.017), emotional awareness ( p  = 0.039), and trusting ( p  = 0.047). PCS‐rumination correlated with MAIA‐positive total ( p  = 0.012). In contrast, better attention regulation signified less improvement in ODI ( p  = 0.043) and MPQ affective ( p  = 0.026). Conclusions: Higher interoceptive awareness in SCS patients correlated with greater improvement following the procedure, particularly with regards to pain relief and pain catastrophizing. These findings suggest that patients with better mind–body connections may achieve greater pain relief following SCS in this patient population, thereby aiding providers in determining who may benefit from this intervention.